Morphology and Biometric Aspect of Trachea and Lungs of Rhesus Monkey (Macaca mulatta) - Jasvinder Singh Sasan; Kamal Sarma; Shalini Suri (Indian Journal of Veterinary Anatomy, 2024)
Trachea was composed of 25-26 C-shaped tracheal rings, joined to one another by annular ligaments. Gap between free ends of C-shaped tracheal rings on dorsal side was completed by connective tissue and trachealis muscle. The length of trachea was 9.7 cm. Tracheal rings were circular in outline cranially, triangular at middle and elliptical in caudal region of trachea. Right lung was grayish in colour whereas the left lung was reddish brown in colour. Both the lungs were divided into distinct lobes by deep interlobar fissures that extended upto the level of hilus. Right lung had apical, cardiac, accessory and diaphragmatic lobe. Diaphragmatic lobe was the largest. Apical lobe was undivided. Accessory lobe was further divided into two parts. Left lung had apical and diaphragmatic lobe. Apical lobe was further divided into cranial and caudal parts by a well-developed fissure and forming a cardiac notch which was L-shaped. Anterior-most border of apical lobe was more rounded in the right lung as compared to the left one. Distinct impressions of ribs were seen over the costal surface of left lung while they were indistinct over the right side. Mediastinal surface presented hilus and cardiac impression. Cardiac impression was more distinct over left lung. Dorsal part of mediastinal surface of left lung showed longitudinal depression left by the aorta. Right lung presented two complete interlobar fissures. On left side, cranial fissure did not extend marked upto the hilus whereas the caudal fissure was complete and separated the caudal part of apical lobe and diaphragmatic lobe.